Comprehensive immunophenotyping of solid tumor-infiltrating immune cells reveals the expression characteristics of LAG-3 and its ligands - Garman, Bradley; Jiang, Can; Daouti, Sherif; Kumar, Sanah; Mehta, Priyanka; Jacques, Miye K.; Menard, Laurence; Manjarrez-Orduno, Nataly; Dolfi, Sonia; Mukherjee, Piali; Rai, Sharmila Chamling; Lako, Ana; et al. (Frontiers in Immunology, 2023)
Immune cell expression profiling from patient samples is critical for the successful development of immuno-oncology agents and is useful to understand mechanism-of-action, to identify exploratory biomarkers predictive of response, and to guide treatment selection and combination therapy strategies. LAG-3 is an inhibitory immune checkpoint that can suppress antitumor T-cell responses and targeting LAG-3, in combination with PD-1, is a rational approach to enhance antitumor immunity that has recently demonstrated clinical success. Here, we performed comprehensive highparameter immunophenotyping of tumor-infiltrating lymphocytes (TILs) and peripheral blood mononuclear cells (PBMCs) from a variety of solid tumor types to identify immune cell subsets that express LAG-3 and its ligands, and to characterize the marker expression profile of these subsets. LAG-3 was most highly expressed by subsets of tumor-infiltrating CD8 T central memory (TCM) and effector memory (TEM) cells and was frequently co-expressed with PD-1. Additionally, we determined that these PD-1 + LAG-3 + CD8 memory T cells exhibited a unique marker profile, with greater expression of activation (CD69, HLA-DR), inhibitory (TIM-3, TIGIT, CTLA-4) and stimulatory (4-1BB, ICOS) markers compared to cells that expressed only PD-1 or LAG-3, or that were negative for both checkpoints. In contrast to tumors, LAG-3 expression was limited in circulating immune cells from healthy donors and solid tumor patients. Additionally, we found abundant expression of the LAG-3 ligands MHC-II and galectin-3 in diverse immune cell types, whereas FGL1 and LSECtin were minimally expressed by immune cells in the tumor microenvironment (TME). Lastly, profiling of circulating immune cells by single cell RNA-seq in a clinical trial cohort of melanoma patients revealed an inverse relationship between baseline and ontreatment levels of circulating LAG3-expressing CD8 memory T cells and response to combination PD-1 and CTLA4 blockade. These results provide insights into the nature of LAG-3-and ligandexpressing immune cells within the TME, and suggest a biological basis for informing mechanistic hypotheses, treatment selection strategies, and combination immunotherapy approaches to support continued development of dual PD-1 and LAG-3 blockade.